Enhancing Adolescent Resilience Against Drug Abuse: A Critical Review of Government Policies and the Role of External Support Systems in Indonesia - Akustyo, Bagus Ridho; Poerwandari, Elizabeth Kristi (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to critically review the policies for enhancing adolescent resilience in preventing drug abuse in Indonesia to address the increasing prevalence of drug abuse among adolescents. The research employs a qualitative approach with data collection methods including literature review and interviews, and uses Nvivo 15 software to organize, code, and analyze the data. The results show that the current policies implemented by the government focus more on interventions aimed at adolescents' internal factors than on external factors. This situation prevents the issue of rising drug abuse among adolescents from being effectively addressed, as the main factors of vulnerability and resilience strengthening lie in external factors. This study contributes by expanding the theory that can be used in policy formulation to improve adolescents' resilience in preventing drug abuse. Additionally, the study enriches the literature on the importance of strengthening support from adolescents' external environments to help them cope with vulnerabilities and enhance their resilience in preventing drug abuse.